Asymptotics for the product of normed maxima - Aksomaitis, Algimantas Pranas; Vilkas, Robertas (Lietuvos matematikos rinkinys, 2000)
Asymptotical analysis for the product of normed maxima of random variables is presented. One particular case for samples of size N , having geometrical distribution, is discussed.